The designers. - Charney, Nicolas H.; Cardin, Marlene McGinnis (Fashion studies online: the Videofashion library, 2003)
With her extraordinary uptown elegance, Carolina Herrera adds a new fragrance and an unbeatable bridal series to her twenty marvelous years of designing the most original styles for the feminine woman of today.